P-032 Vascular reconstruction devices shrink small cerebral aneurysms. (12th July 2011) - Nyberg, E; Larson, T
Abstract : Endovascular treatment of intracranial aneurysms (IAs) often includes the deployment of a vascular reconstruction device (VRD), particularly if the aneurysm has a wide neck or unfavorable dome to neck ratio, to prevent coil herniation and to facilitate increased packing density. However other benefits may be hemodynamic and physiologic, that is, through flow diversion, reduced wall shear stress (WSS), and the provision of a scaffolding to support endotheliazation over the aneurysm neck. Hemodynamic simulations using computational flow dynamics suggest that the effect of flow diversion exerted by the Enterprise VRD decreases flow velocity in the aneurysm, increases stasis and decreases WSS, however to our knowledge clinical examples have not been published. We present four cases of staged, elective treatment of small saccular intracranial aneurysms in which placement of a single Enterprise VRD or Wingspan stent alone prompted beneficial aneurysm remodeling such that by the time of the planned coiling several weeks later these aneurysms had substantially decreased in size and it was felt that coil embolization was no longer feasible. We surmise that the VRDs in our series improved hemodynamic conditions enabling aneurysm shrinkage. This may have been accomplished in part by flow diversion by the device struts as simulations have predicted. However, another mechanism of remodeling may involve changing the geometry of the aneurysm and parent vessel. Increased WSS and WSS gradients are often found at vascular branch points or curvatures, therefore straightening of the parent vessel may be beneficial in these cases. All patients in our series demonstrated some degree of vessel straightening. Protrusion of device struts into the dome may also play a beneficial role. In summary, benefits of VRDs not directly related to coil packing may include flow diversion allowing for thrombotic retraction of the dome as well as decreased WSS and WSS gradients due to vessel straightening. Thus staging treatment in this manner may allow the aneurysm to shrink in some patients, thereby avoiding the risk of coil embolization. The long term prognosis of these tiny aneurysm remnants is unknown and these patients clearly need to be followed. Furthermore, whatever hemodynamic effects single VRDs may exert are unlikely to be effective in larger aneurysms, perhaps >3 mm.